Methylprednisolone Protects Cardiac Pumping Mechanics from Deteriorating in Lipopolysaccharide-Treated Rats - Ko, Ya-Hui; Tsai, Ming-Shian; Chang, Ru-Wen; Chang, Chun-Yi; Wang, Chih-Hsien; Wu, Ming-Shiou; Liang, Jin-Tung; Chang, Kuo-Chu (Frontiers in Physiology, 2015)
It has been shown that a prolonged low-dose corticosteroid treatment attenuates the severity of inflammation and the intensity and duration of organ system failure. In the present study, we determined whether low-dose methylprednisolone (a synthetic glucocorticoid) can protect male Wistar rats against cardiac pumping defects caused by lipopolysaccharide-induced chronic inflammation. For the induction of chronic inflammation, a slow-release ALZET osmotic pump was subcutaneously implanted to infuse lipopolysaccharide (1 mg kg−1 d−1) for 2 wk. The lipopolysaccharide-challenged rats were treated on a daily basis with intraperitoneal injection of methylprednisolone (5 mg kg−1 d−1) for 2 wk. Under conditions of anesthesia and open chest, we recorded left ventricular (LV) pressure and ascending aortic flow signals to calculate the maximal systolic elastance (Emax) and the theoretical maximum flow (Qmax), using the elastance-resistance model. Physically, Emax reflects the contractility of the myocardium as an intact heart, whereas Qmax has an inverse relationship with the LV internal resistance. Compared with the sham rats, the cardiodynamic condition was characterized by a decline in Emax associated with the increased Qmax in the lipopolysaccharide-treated rats. Methylprednisolone therapy increased Emax, which suggests that the drug may have protected the contractile status from deteriorating in the inflamed heart. By contrast, methylprednisolone therapy considerably reduced Qmax, indicating that the drug may have normalized the LV internal resistance. In parallel, the benefits of methylprednisolone on the LV systolic pumping mechanics were associated with the reduced cardiac levels of negative inotropic molecules such as peroxynitrite, malondialdehyde, and high-mobility group box 1 protein. Based on these data, we suggested that low-dose methylprednisolone might prevent lipopolysaccharide-induced decline in cardiac intrinsic contractility and LV internal resistance, possibly through its ability to reduce the aforementioned myocardial depressant substances. However, since our results were obtained in anesthetized open-chest rats, extrapolation to what may occur in conscious intact animals should be done with caution.